Travelling models and the challenge of pragmatic contexts and practical norms: the case of maternal health - Jean-Pierre Olivier de Sardan; Aïssa Diarra; Mahaman Moha (BMC, 2017)
Abstract As in other areas of international development, we are witnessing the proliferation of 'traveling models' developed by international experts and introduced in an almost identical format across numerous countries to improve some aspect of maternal health systems in low- and middle-income countries. These policies and protocols are based on 'miracle mechanisms' that have been taken out of their original context but are believed to be intrinsically effective in light of their operational devices. In reality, standardised interventions are, in Africa and elsewhere, confronted with pragmatic implementation contexts that are always varied and specific, and which lead to drifts, distortions, dismemberments and bypasses. The partogram, focused antenatal care, the prevention of mother-to-child transmission of HIV or performance-based payment all illustrate these implementation gaps, often caused by the routine behaviour of health personnel who follow practical norms (and a professional culture) that are often distinct from official norms - as is the case with midwives. Experiences in maternal and child health in Africa suggest that an alternative approach would be to start with the daily reality of social and practical norms instead of relying on models, and to promote innovations that emerge from within local health systems.